Makroharmonia i centryczność - Tymoczko, Dmitri; Iwańska, Ilona (Res Facta Nova, 2025)
Polish translation of Dmitri Tymoczko, Macroharmony and Centricity, chapter 5. in: A Geometry of Music. Harmony and Counterpoint in the Extended Common Practice, Oxford University Press, 2011.